Cold snare endoscopic mucosal resection for colon polyps: a systematic review and meta-analysis - Abdallah, Mohamed; Ahmed, Khalid; Abbas, Daniyal; Mohamed, Mouhand F. H.; Suryawanshi, Gaurav; McDonald, Nicholas; Wilson, Natalie; Umar, Shifa; Shaukat, Aasma; Bilal, Mohammad (Endoscopy, 2023)
Background Cold snare endoscopic mucosal resection (CS-EMR) can reduce the risks associated with electrocautery during colon polyp resection. Data on efficacy are variable. This systematic review and meta-analysis aimed to estimate the pooled efficacy and safety rates of CS-EMR.Methods We conducted a comprehensive literature search of multiple databases, from inception to March 2023, for studies addressing outcomes of CS-EMR for colon polyps. The weighted pooled estimates with 95 %CIs were calculated using the random effects model. I2 statistics were used to evaluate heterogeneity.Results 4137 articles were reviewed, and 16 studies, including 2592 polyps in 1922 patients (51.4 % female), were included. Overall, 54.4 % of polyps were adenomas, 45 % were sessile serrated lesions (SSLs), and 0.6 % were invasive carcinomas. Polyp recurrence after CS-EMR was 6.7 % (95 %CI 2.4 %–17.4 %, I2 = 94 %). The recurrence rate was 12.3 % (95 %CI 3.4 %–35.7 %, I2 = 94 %) for polyps ≥ 20 mm, 17.1 % (95 %CI 4.6 %–46.7 %, I2 = 93 %) for adenomas, and 5.7 % (95 %CI 3.2 %–9.9 %, I2 = 50 %) for SSLs. The pooled intraprocedural bleeding rate was 2.6 % (95 %CI 1.5 %–4.5 %, I2 = 51 %), the delayed bleeding rate was 1.5 % (95 %CI 0.8 %–2.7 %, I2 = 18 %), and no perforations or post-polypectomy syndromes were reported, with estimated rates of 0.6 % (95 %CI 0.3 %–1.3 %, I2 = 0 %) and 0.6 % (95 %CI 0.3 %–1.4 %, I2 = 0 %), respectively.Conclusion CS-EMR demonstrated an excellent safety profile for colon polyps, with variable recurrence rates based on polyp size and histology. Large prospective studies are needed to validate these findings.